Cracking the code of Earth's magnetic mysteries: ancient secrets unveiled by byzantine bricks reconfirmed by Mesopotamian ceramics - Ioannis Liritzis (Proceedings (European Academy of Sciences and Arts))
The study of the magnetization of artifacts discovered at archaeological sites, such as ceramics or hearth remnants, is known as archaeomagnetism. This technique is based on the idea that some materials get magnetized in the direction and intensity of the Earth's magnetic field at the time when heated or exposed to extreme heat. Development in the field has been made to improve magnetometer devices and sample size, as well as measuring techniques of thermal remanent magnetization. It helped to study the variation of the complex Earth’s magnetic field or geomagnetic field (GMF) for both geophysical and archaeological dating benefits. The rapid change in GMF within a few hundred or decades, as being of genuine origin or methodological and sample unsuitability has been a matter of debate. Data from about 40 years ago derived from well-dated Byzantine churches that first confirmed such geomagnetic spikes is discussed along with recent archaeomagnetic data from Mesopotamian inscribed bricks and Levantine slags.